Association of the chromosome replication initiator DnaA with the Escherichia coli inner membrane in vivo: quantity and mode of binding. - Tomer Regev (Public Library of Science (PLoS), 2012)
DnaA initiates chromosome replication in most known bacteria and its activity is controlled so that this event occurs only once every cell division cycle. ATP in the active ATP-DnaA is hydrolyzed after initiation and the resulting ADP is replaced with ATP on the verge of the next initiation. Two putative recycling mechanisms depend on the binding of DnaA either to the membrane or to specific chromosomal sites, promoting nucleotide dissociation. While there is no doubt that DnaA interacts with artificial membranes in vitro, it is still controversial as to whether it binds the cytoplasmic membrane in vivo. In this work we looked for DnaA-membrane interaction in E. coli cells by employing cell fractionation with both native and fluorescent DnaA hybrids. We show that about 10% of cellular DnaA is reproducibly membrane-associated. This small fraction might be physiologically significant and represent the free DnaA available for initiation, rather than the vast majority bound to the datA reservoir. Using the combination of mCherry with a variety of DnaA fragments, we demonstrate that the membrane binding function is delocalized on the surface of the protein's domain III, rather than confined to a particular sequence. We propose a new binding-bending mechanism to explain the membrane-induced nucleotide release from DnaA. This mechanism would be fundamental to the initiation of replication.